The synthesis, characterization and activation of some multinuclear catalyst precursors for olefin polymerization - Waggie, Fazlin (Department of Chemistry, 2023)
This thesis reports on an exploratory investigation into the immobilization of homogeneous olefin polymerisation cataiysts on dendritic supports...; The dendrimers . employed were essentially allylaryl-ether type systems and consisted of both dendritic wedges .and compltte dendrimers.. These materials were used as supports for homogeneous irconocene catalysts. The zirconium moiety was attached to the surface of the dendrimer through the ally! functionality. This was dope via hydrozirconation of the pendant C=C of the ally! groups on the periphery of the dendrimers. A number of model compounds such as Cp2Zr{(CH2)4iPh}(Cl) and Cp2Zr{(CH2)30Ph}(Cl) were also prepared and their pronerties compared with the dendritic catalyst precursors .. The supported catalyst species together with. analogous mononuclear model compounds were activated using a range of activating agents. Included amongst these activating agents are, silver salts of the type AgX, (where X = OS02CF3, Cl04 and BP); the perfluoroaryl borane, B(C6Fs)3 and MAO. The activated complexes were assessed for their. polymerisation ability towards ethylene. The dendrimers were characterised using techniques such as FTIR spectroscopy, 1 H NMR and 13C NMR spectroscopy, GC mass spectrometry and microanalysis. All new organometallic compounds produced were characterised using techniques such as 1 H NMR and 13C NMR spectroscopy. The polymers prepared were characterised by Gel Permeation Chromatography (GPC), Fourier Transform InfraRed (FTIR), 1 H and 13C NMR spectroscopy, Differential Scanning Calorimetry (DSC) as well as Scanning Electron Microscopy (SEM).